Development of Electrical Lighting Installation Jobsheet at SMKN 4 Kota Serang - Prestanty, Deva Adelya; Wardoyo, Siswo; Fatkhurrokhman, Mohammad (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to produce an electrical lighting installation jobsheet, in order to determine the level of feasibility and effectiveness in learning activities at SMKN 4 Kota Serang. This study uses the Research and Development (R&D) research method. This study conducted a feasibility test with media expert validation obtaining an average score of 3.83 in the